Sakhalin Ainu Inferentials as Indicators of Relative Tense - Elia Dal Corso (Edizioni Ca' Foscari, 2025)
This paper investigates inferential evidentiality in Sakhalin Ainu with a specific focus on the pragmatic use of inferential forms to bring out the tense reference of the predicate that is under the scope of evidentiality. It will be argued that what derives either a present or past tense reference for the scope predicate is the interplay of the telicity and aspectual values of the scope predicate itself, and the inner semantics of the inferential form used. Together with these two semantic variables, another pivotal element involved in the derivation of tense reference is the very cognitive process that is entailed by acquisition of information through inference. As it is chiefly concerned with tense and aspect, this study contributes to the description of the tense-aspect- mood-evidentiality (TAME) system of Sakhalin Ainu and Ainu more generally, which has traditionally been described as a ‘tenseless’ language.